Sectoral dimension of employment targeting - Tregenna, Fiona (Geneva, 2015)
"This paper presents a rationale for analysing employment by taking the sectoral structure of an economy into consideration. It provides an overview of ways of measuring employment intensity and discusses the relationship between employment intensity and labour productivity. It uses the South African experience for empirical illustrations of substantive propositions."